Growth and dry matter partitioning in potatoes as influenced by paclobutrazol applied to seed tubers (2020)
Under cultivation conditions that favor the growth of plant shoots, the adoption of management practices that reduce the size of potato plants can be an alternative for increasing tuber yield. The objective of this study was to evaluate the effect of paclobutrazol on vegetative growth and dry matter partitioning in the potato plant cv. Markies, cultivated under summer conditions in the state of Minas Gerais. The treatments were 0.1, 1.0, 10 and 100 mg L-1 of paclobutrazol (PBZ), applied to sprouted seeds before planting and control with water. PBZ was efficient in reducing plant height. The PBZ treatments with doses of 10 and 100 mg L-1 delayed the emergence of shoots and the beginning of plant tuberization. PBZ at 0.1 mg L-1 reduced the lengh of the stem by 18% but did not differ from the control for the fresh and dry mass content, total production, specific gravity and starch content of tubers. The treatment with seed potatoes and PBZ at 0.1 mg L-1 resulted in smaller, more compact plants, which could be suitable for more densely planted cultivations in order to maximize plant populations and increase economic return per unit of area.